Perilaku Organisasi Sekolah dalam Menghadapi Perubahan Kurikulum di UPT SMP N 27 Medan - Lilis Julianty; Lathifatun Nisa Hutabarat; Maulana Hakim (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to analyze the behavior of school organizations in facing curriculum changes at UPT SMP N 27 Medan. Curriculum change is a challenge that requires adaptation from all school elements, including teachers, principals and support staff. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews and documentation. The research focus includes how school organizations behave in responding to curriculum changes, the strategies implemented to manage changes, and the obstacles faced during the adaptation process. It is hoped that the research results will provide an overview of the dynamics of school organizations in the context of curriculum change as well as recommendations for effective management of change in the school environment.